1998
DOI: 10.1246/bcsj.71.1825
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatography Stationary Phases Based on π–π Electron Interaction. Aminopropyl Silica Gels Modified with Metal Phthalocyanines

Abstract: Aminopropyl silica gels were modified with two porphyrin derivatives and five phthalocyanine derivatives. The modified silica gels were evaluated for the usefulness as high-performance liquid chromatography stationary phases for the separation of π-electron-rich polyaromatic hydrocarbons (PAHs) such as naphthalene and phenanthrene. As a result of the modification, the aminopropyl silica gels acquired a function of π–π electron interaction with PAHs. In particular, the aminopropyl silica gel modified with coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Desta forma, as propriedades destas sílicas modificadas quimicamente sofreram alterações, que puderam ser exploradas em várias atividades acadêmicas ou tecnológicas. Assim, a sílica organofuncionalizada encontra principalmente aplicações como fase estacionária para cromatografia [18][19][20][21] ou suporte para materiais com propriedades catalíticas [22][23][24][25][26][27][28][29] . Uma destacada utilização consiste no uso da molécula imobilizada como agente sequestrante para metais, que será enfocado aqui.…”
Section: Figura 1 Esquema Dos Tipos De Grupos Silanóis Normalmente Eunclassified
“…Desta forma, as propriedades destas sílicas modificadas quimicamente sofreram alterações, que puderam ser exploradas em várias atividades acadêmicas ou tecnológicas. Assim, a sílica organofuncionalizada encontra principalmente aplicações como fase estacionária para cromatografia [18][19][20][21] ou suporte para materiais com propriedades catalíticas [22][23][24][25][26][27][28][29] . Uma destacada utilização consiste no uso da molécula imobilizada como agente sequestrante para metais, que será enfocado aqui.…”
Section: Figura 1 Esquema Dos Tipos De Grupos Silanóis Normalmente Eunclassified
“…8,9) On the other hand, it has been reported that a silica-based M-PCS D column, wherein metal phthalocyanine sulfonic acid derivative (M-PCS) is immobilized on silica gels, and of which separation mechanism is principally based on the p-p interaction in a polar solvent (e.g., methanol-water system), is useful for separations of PAHs. [13][14][15][16] In the M-PCS D , metal phthalocyanine is immobilized on silica gels in a horizontal manner, and the immobilization makes greater planar recognition ability than that of the PYE column ® . 14,15) Generally, PAHs having many aromatic rings are slightly/poorly soluble in a polar solvent, and, therefore, PAHs are usually extracted with a non-polar eluent before applying to HPLC.…”
mentioning
confidence: 99%
“…As for the Cu-PCS r column, the ∆RT increased remarkably with an increase in the ring number, indicating that the larger PAHs interacted more strongly with Cu-PCS, similarly to the case of the silica gel modified with Cu-phthalocyanine derivative. [1][2][3] This should be attributable to the interaction between π-electron clouds of Cu-PCS and PAHs.…”
Section: Separation Of Benzene and Polyaromatic Hydrocarbons (Pahs)mentioning
confidence: 99%